Topology of diffusion changes in corpus callosum in Alzheimer's disease: an exploratory case-control study - Kumar, Sumeet (2023)
This study aims to assess the integrity of white matter in various segments of the corpus callosum in Alzheimer's disease (AD) by using metrics derived from diffusion tensor imaging (DTI), diffusion kurtosis imaging (DKI) and white matter tract integrity model (WMTI) and compare these findings to healthy controls (HC).